Can Adults Accurately Judge Child Weight Status? - Bethany J. Ridley; Kristofor McCarty; Robin S. S. Kramer; Martin J. Tovée; Piers L. Cornelissen (Children, 2025)
Background/objectives: This study addresses two questions: what body sizes/shapes do participants believe correspond to the boundaries of the National Child Measurement Programme (NCMP) weight categories for children aged 4–5 and 10–11 years old, and are these judgements altered by using terminology encouraging positive action by parents? Methods: The study used photorealistic computer-generated stimuli based on 388 3D scans of children in a method of adjustment task. We first asked participants to estimate the boundaries between weight status categories as described by the NCMP. To test validity, we asked a second set of participants to estimate the body that represented exemplars of each weight category (the exemplars should fall between the boundary estimates). We then recruited a third set of participants to determine whether substituting positive action terminology for the weight status definitions altered the boundary positions. Results: First, validity was confirmed. Second, we found a compressed response range (lower weights overestimated and higher weights underestimated) for the positioning of both categorical boundaries and exemplars. Finally, the use of alternative weight status terminology resulted in an upward shift in the position of all boundaries in the BMI spectrum but failed to remove the compressive stimulus response effect. Discussion: There is a disconnect between the child size that people perceive to correspond to the different weight categories and the size criteria used by health professionals, and it is likely that this gap can only be bridged by training to recognise the medically based categories.